Avulsion fracture associated with desmite of the straight sesamoid ligament in a mare: diagnosis, treatment and prognosis (Research, Society and Development, 2022)
Injuries to the sesamoid ligaments can occur in horses practicing various modalities, such as racehorses being the most prone to alterations in these structures. In addition to the clinical examination, ultrasound and radiographic images can be used to diagnose possible changes in the sesamoid ligaments and bone structures. The purpose of this study was to report the clinical, radiographic and sonographic findings, as well as the therapy and outcome of a case of straight sesamoid ligament desmitis associated with avulsion fracture in horse. A mare, Quarter Horse, 5 years old, 450 kg, suddenly presented with severe lameness of the right forelimb. The animal presented claudication grade 4/5 (AAEP), increased temperature and pain on palpation in the palmar aspect of the quarter. On radiographic examination, a slight irregularity in the palmaroproximal aspect of the intermediate phalanx and an area of bone resorption associated with an irregularity in the flexor tuberosity of the intermediate phalanx was observed. In the ultrasonographic evaluation of the palmar region of the chin, it was observed the presence of areas of irregularity in the insertion of the middle scutum associated with the presence of bone fragments in the flexor tuberosity of the intermediate phalanx, as well as an increase in the size of the straight ligament and areas of fiber rupture. The use of phenylbutazone and rest for four months were indicated. When reassessed after two months, the animal presented claudication grade 2/5 (AAEP), with no positive response to palpation of the hip and forced flexion of the digit. In the case reported, the clinical examination associated with radiographic and ultrasound images were sufficient to determine the final diagnosis and subsequent prescription of the appropriate treatment. The therapy based on non-steroidal anti-inflammatory and rest proved to be effective in reducing clinical signs.